POTENTIAL OF CELLULASE OF CHAETOMIUM GLOBOSUM FOR PREPARATION AND CHARACTERIZATION OF MICROCRYSTALLINE CELLULOSE FROM WATER HYACINTH (EICHHORNIA CRASSIPES) - SURYADI, HERMAN; INDAH LESTARI, YULIANITA PRATIWI; MIRAJUNNISA; YANUAR, ARRY (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to increase the yield of microcrystalline cellulose (MCC) made from water hyacinth ɑ-cellulose by enzymatic hydrolysis by using purified enzyme and to find it’s characteristics compared to the reference. Methods: In this research, MCC was prepared from water hyacinth powder through the chemical isolation process of ɑ-cellulose, followed by enzymatic hydrolysis with purified cellulase from Chaetomium globosum. The yield of MCC was improved by using purified enzyme and optimization of temperature, pH, and hydrolysis time. Identification was carried out by using ZnCl and infrared spectrophotometry, followed by characterization of MCC include particle size analysis (PSA) and diffractogram pattern (X-Ray Diffraction) compared to reference Avicel PH 101. Results: Purified enzyme from Chaetomium globosum has high activity with a clear zone area of 45 mm with cellulolytic index 6.5 that almost same as Trichoderma reesei (50 mm), with the cellulase enzyme activity of 6.691 U/ml. The optimum condition was at a temperature of 50⁰C and pH 6.0 with the hydrolysis time of 2 h, which produced 95% yield of MCC. Identification with ZnCl and FTIR spectrum showed positive results, similar to the reference. The results of organoleptic test, particle size analysis, and diffractogram pattern (X-Ray Diffraction) showed crystalline characteristic similar to reference (Avicel PH 101). Conclusion: Enzyme from Chaetomium globosum has a higher activity of cellulase than Trichoderma reesei with MCC obtained was 95%. Based on the comparison of the organoleptic test, particle size analysis, and diffractogram pattern, MCC from water hyacinth has a great potential which showed similar characteristic to reference (Avicel pH 101).